Bolivia: La experiencia populista de los a\~nos ochenta - Juan Antonio Morales (Universidad Católica Boliviana, Instituto de Investigaciones Socio-Económicas (IISEC), 2008)
– In late 1982 Bolivia returned to democracy, after a long period of mostly military governments, during whose tenure real wages had declined considerably. The first democratic government, presided by Dr. Hernán Siles Suazo inherited of the military governmets a much deteriorated economy, marked by the external debt crisis. Siles Zuazo found very difficult to mediate between macroeconomic adjustment and the demands of his electorate. The government's defensive populism was unable to cope with the mounting social pressures that affected the fiscal deficits which were financed printing money. The resulting inflation that culminated in hyperinflation was moreover accompanied by food shortages and black markets. GDP fell substantially. The Central Confederation of Workers disdained the fiscal and balance of payments constraints and its wage race was a major culprit of the economic disaster. The hyperinflation was stopped with a drastic and orthodox program of stabilization that a side result politically weakened organized labor.
Keywords: 330